A single center experience: rituximab plus cladribine is an effective and safe first-line therapy for unresectable bronchial-associated lymphoid tissue lymphoma - Wei, Zheng; Li, Jing; Cheng, Zhixiang; Yuan, Ling; Liu, Peng (Journal of Thoracic Disease, 2017)
Background: Bronchial-associated lymphoid tissue (BALT) lymphoma is a relatively rare form of B-cell non-Hodgkin lymphoma (B-NHL). To date, the standard systemic treatment for this disease is still under debate, and few data are accessible for newly diagnosed unresectable BALT lymphoma presented with advanced disease. The combination of rituximab (R) and cladribine (2-CdA) has shown some activity in indolent B-NHL, but its usage has not been tested in disseminated BALT lymphoma so far. Methods: An observational retrospective study was performed on homogeneous data of 8 patients with biopsy-proven stage IV BALT lymphoma to assess the efficacy and the safety of R-2-CdA therapy. All but one of the patients received six courses of R-2-CdA regimen consisted of rituximab 375 mg/m2 IV day 1 and cladribine 0.1 mg/kg IV days 1–4 every 21 days; one patient completed 4 cycles and received additional R maintenance. Results: A high overall response rate (ORR) was observed (100%), with 2 patients (25%) achieved a complete remission (CR), the remaining (75%) a partial response. Improvement of pulmonary function was observed in all tested patients. Grade 3 and 4 toxicities were leukocytopenia and neutropenia in 3 patients (37.5%), diarrhea in one (12.5%). Estimated two-year progression-free survival (PFS) and 2-yr overall survival (OS) were 80.0% (95% CI, 20.3–96.7%) and 100%, respectively. Conclusions: R-2-CdA therapy demonstrated high activity and tolerable toxicity in chemotherapy-naïve patients with unresectable BALT lymphoma of advanced stage. Although further large-scale study is needed for consolidation, R-2-CdA regimen could be a good first-line therapy option for patients with unresectable BALT lymphoma.